Designing for sustainability through upcycling : learning from Paleiskwartier, Netherlands = Ontwerpen voor duurzaamheid door herontwikkeling : leren van Paleiskwartier, Nederland - Khandekar, Shyam; Bharne, Vinayak; Mulder, Joost (2020)
"While increasingly more people live in cities, urban peripheries are expending at the cost of nature. This book explains how sustainability can be achieved by urban redevelopment and upcycling. The large-scale processes of urban redevelopment in this book are based on a successful brownfield project in Netherlands, the Paleiskwartier in 's-Hertogenbosch. 'Designing for sustainability through upcycling' tells the inside story of nearly three decades how policies were made, decisions taken, designs created, how the projects developed in phases and how the city government partnered the private sector in a unique way. A series of essays and short interviews with key players involved - including directors, designers, developers and city-officials - provides a detailed overview of how this project was actually realized. This book offers first-hand information of 30 years of development as told by master-planner Shyam Khandekar. Professor Vinayak Bharne places the process of upcycling in the context of developments from other parts of the world. A must-read for those on the threshold of undertaking a brownfield redevelopment process in their city"--Page 4 of cover.
"MyLiveableCity".
In English and parallel Dutch text.
Keywords: Urban renewal -- Netherlands; Sustainable urban development -- Netherlands